2018
DOI: 10.1037/xge0000418
|View full text |Cite
|
Sign up to set email alerts
|

It’s all about gains: Risk preferences in problem gambling.

Abstract: Problem gambling is a serious socioeconomic problem involving high individual and social costs. In this article, we study risk preferences of problem gamblers including their risk attitudes in the gain and loss domains, their weighting of probabilities, and their degree of loss aversion. Our findings indicate that problem gamblers are systematically more risk taking and less sensitive toward changes in probabilities in the gain domain only. Neither their risk attitudes in the loss domain nor their degree of lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 90 publications
8
18
1
Order By: Relevance
“…The group differences in EV sensitivity were observed in both gain and loss-related choices. A group difference in GD on the loss version of the task is contrary to some other findings (Brevers et al, 2012;Ring et al, 2018;van Holst, Veltman, B€ uchel, Van Den Brink, & Goudriaan, 2012). Notably, in contrast to these previous experiments investigating loss-based decision making and aversive (threat of shock) processing (Brevers et al, 2012;Ring et al, 2018), the present study entailed more complex decisions between two risky lotteries, rather than choices between a certain outcome and a risky lottery.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…The group differences in EV sensitivity were observed in both gain and loss-related choices. A group difference in GD on the loss version of the task is contrary to some other findings (Brevers et al, 2012;Ring et al, 2018;van Holst, Veltman, B€ uchel, Van Den Brink, & Goudriaan, 2012). Notably, in contrast to these previous experiments investigating loss-based decision making and aversive (threat of shock) processing (Brevers et al, 2012;Ring et al, 2018), the present study entailed more complex decisions between two risky lotteries, rather than choices between a certain outcome and a risky lottery.…”
Section: Discussioncontrasting
confidence: 84%
“…We had no a priori prediction as to whether this would be due to altered processing of probability information, magnitude information, or preceding feedback. We predicted that group differences would be present in both gain and loss conditions, but we tested for any asymmetry (Brevers et al, 2012;Ring et al, 2018). Within the group with gambling disorder, we further expected that the sensitivity to EV information would be correlated with increasing problem gambling severity and increasing levels of gambling-related cognitive distortions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vieider et al (2018) and Vieider et al (2019) used the same tasks and showed that they systematically correlated with demographic characteristics and economic behavior. Another study using the same method shows that gamblers' risk preferences were different than healthy subjects in the gain domain (Ring et al 2018).…”
Section: Experimental Designmentioning
confidence: 99%